Nonlinear modeling and circuit optimization of GaAs MESFET oscillators - Ochave, Victorio E. A. (1996)
A nonlinear optimization procedure to design power-optimum GaAs MESFET microwave oscillators is investigated and implemented in this thesis. The method aims to eliminate the empirical nature of microwave oscillator design. To carry out the procedure, a large-signal GaAs MESFET model is constructed; the model simulates device breakdown and accounts for the frequency dispersive behavior of output conductance. A direct extraction of small-signal model elements is undertaken, while the large-signal model parameters are obtained using a simultaneous fitting of measured device DC and RF data to nonlinear expressions representing optimizer in conjunction with a quasi-Newton scheme is employed in the extraction of the large-signal model parameters. The harmonic balance method is used to compute the steady-state terminal currents, while a coupled random-gradient optimizer is used to search for the optimum device port voltages that will induce the device to operate at prespecified conditions. The nonlinear design method is shown to result in GaAs MESFET oscillator designs that operate nearer the desired frequency of operation and with higher RF output power, compared to circuits designed using conventional methods.
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Oscillators, Microwave; Metal semiconductor field-effect transistors; Oscillators, Electric